Plecoptera from Minas Gerais State, southeastern Brazil - Novaes, Marcos Carneiro; Bispo, Pitágoras Da Conceição (Zootaxa, 2014)
Specimens of Plecoptera collected in Minas Gerais State, Brazil were studied. Twelve previously described species were identified, Anacroneuria boraceiensis Froehlich, 2004, A. debilis (Pictet, 1841), A. itatiaiensis Baldin et al., 2013, A. polita (Burmeister, 1839), A. singularis Righi-Cavallaro & Lecci, 2010, A. stanjewetti Froehlich, 2002, A. terere Righi-Cavallaro & Lecci, 2010, A. vanini Froehlich, 2004, Kempnyia neotropica (Jacobson and Bianchi, 1905), K. obtusa Klapálek, 1916, Tupiperla gracilis (Burmeister, 1839) and T. robusta Froehlich, 1998. Additionally, two new species of Anacroneuria are described, A. paprockii n. sp. and A. mineira n. sp., and a list of species from Minas Gerais State is presented.